Effects of Added Copper and Zinc on Growth Performance and Carcass Characteristics of Finishing Pigs Fed Diets with or without Ractopamine HCl - J. A. Feldpausch; R. G. Amachawadi; H. M. Scott; M. D. Tokach; S. S. Dritz; J. C. Woodworth; T. G. Nagaraja; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 480 pigs (PIC 327 × 1050; initially 107.4 lb) were used to determine the interactive effects of supplemental Cu, Zn, and Ractopamine HCl on finishing pig growth performance, carcass characteristics, and antimicrobial susceptibility of enteric bacteria. Dietary treatments were arranged in a 2 × 2 × 2 factorial with main effects of added copper sulfate (CuSO4; 0 vs. 125 ppm Cu), added zinc oxide (ZnO; 0 vs. 150 ppm Zn), and Ractopamine HCl (0 vs. 10 ppm during the last 28 d prior to marketing; Paylean®; Elanco Animal Health, Greenfield, IN). All finishing diets were fed in four phases in meal form and contained 11 ppm Cu and 73 ppm Zn from the trace mineral premix. The study design was structured as a randomized complete block design and replicated with two finishing groups. Pigs were randomly allotted to pens upon entry into the finisher barn. Pens of seven (group 1) or eight (group 2) pigs were balanced on initial BW and randomly allotted to 1 of the 4 mineral treatment diets with two treatment replications per weight block and four weight blocks per finishing group. At 28 d prior to marketing, pens within each block and mineral treatment were randomly assigned to receive either 0 or 10 ppm Ractopamine HCl in addition to the mineral treatment. At the conclusion of the 90-d (group 1) or 83-d (group 2) finishing period, carcass characteristics were measured. Adding Cu or Zn alone resulted in numerical improvements in overall F/G and caloric efficiencies; however, the improvements were not additive (Cu × Zn, P = 0.065, 0.068, and 0.064 for F/G and caloric efficiency on a ME and NE basis, respectively). No significant improvements were observed in overall ADG or ADFI due to added Cu and/or Zn. In contrast, Ractopamine HCl improved (P<0.001) overall ADG, F/G, and caloric efficiency, thereby increasing final BW by 3% with no change in ADFI. Ractopamine HCl also increased (P<0.001) HCW, percentage carcass yield, and HCW F/G. Adding Zn or Cu alone to diets containing Ractopamine HCl numerically improved percentage carcass yield and HCW F/G, but this effect was not present when the mineral was added to the control diet or when the minerals were fed in combination in the Ractopamine HCl diets (Cu × Zn × Ractopamine, P = 0.011 and 0.024 respectively). Regardless of HCW, pigs fed Ractopamine HCl had decreased (P = 0.014) backfat, increased (P<0.001) loin depth, and percent fat-free lean. No effects of added minerals on these carcass traits were observed. In summary, the addition of 125 ppm Cu and/or 150 ppm Zn to diets containing Ractopamine HCl failed to improve finishing pig growth performance and carcass characteristics while 10 ppm Ractopamine HCl increased lean tissue deposition and improved feed and caloric efficiency.
Keywords: finishing pig; copper; zinc; Ractopamine